Tissue-Based Research In Kidney Cancer: Current Challenges And Future Directions - Signoretti, Sabina (2008)
The past several years have seen unprecedented advances in the application of various therapeutic strategies for the treatment of patients with renal cancer. The availability of active immunotherapy, anti-angiogenic therapy and targeted therapy for this disease has brought front and center issues related to choosing the appropriate treatment for particular patient populations. It is increasingly evident that the most promising treatment selection strategies will incorporate identifying specific features of the tumor itself. In order to facilitate this move toward personalized medicine, it is critically important to establish some standard principles for renal cancer tissue collection, preparation and analysis for translational research studies. In this article we identify and discuss some critical issues related to tissue-based kidney cancer research. We focus on five major areas: 1) surgical and image-guided techniques for tissue collection 2) quality control of specimen collection, processing, storage and review 3) issues related to analysis of paraffin embedded tissues 4) genomic studies 5) assessment of reproducibility of assays across institutions. In addition, some practical implementation strategies are proposed. While many of the topics discussed are specific for renal cancer, several are also relevant to tissue based biomarker investigations in a broad array of malignancies.